Feminist Philosophy: Time, history and the transformation of thought (Södertörn Academic Studies, 2023)
What is the relationship between feminism and philosophy today? Although feminist philosophy is now a recognized field in the institution of philosophy, a tension between the terms feminism and philosophy persists. From the perspective of philosophy, feminist philosophy may seem too committed to political change. From the perspective of feminism, the practice of philosophy may seem too far removed from the pressing concerns of injustice in ordinary life. This volume is an interdisciplinary initiative at the intersection of philosophy, the history of ideas, and feminist theory, where philosophy is scrutinized from a feminist perspective and asks questions about what philosophy has to offer feminism.